Remanent magnetization and coercivity of rocks under hydrostatic pressure up to 1.4 GPa. Issue 15 (6th August 2013) - Demory, F.; Rochette, P.; Gattacceca, J.; Gabriel, T.; Bezaeva, N. S.
Abstract : [1] We designed an Isothermal Remanent Magnetization (IRM) acquisition system based on permanent magnets and sized to accommodate an amagnetic hydrostatic pressure cell. This pressure cell fits in a superconducting rock magnetometer, allowing for the measurement of remanent magnetization of pressurized samples. With this system, we determined the coercivity of remanence (Bcr ) at different hydrostatic pressures up to 1.4 GPa for rock and dispersed mineral samples with various magnetic mineralogy and domain state. IRM and Bcr are nearly identical before compression and after decompression, indicating no permanent changes in the magnetic properties during pressure cycling. Hydrostatic pressure up to 1.4 GPa does not significantly increases IRM under pressure except for multidomain pyrrhotite and magnetite which show an increase of about 40%. Relative increase of Bcr under pressure is mild, except for a near single domain titanomagnetite where Bcr doubles. Key Points: Pure hydrostatic pressure Isothermal Remanent Magnetization acquisition system Results differ from studies using solid confining media